THE INFLUENCE OF EMPLOYEE COMPENSATION, MOTIVATION AND LOYALTY AS INTERVENING VARIABLES ON PERFORMANCE ORGANIZATION IN CIBINONG CLASS B PRIVATE HOSPITAL - Herda Febtri Ranti; Mohamad Reza Hilmy; Rina Anindita (Jurnal Cinta Nusantara, 2024)
Employees tend to experience high work stress because most of their time is spent at work and with the same job. So that the greater the motivation possessed by individuals as employees can improve the performance of the organization itself. Among management theorists and practitioners, it has long been known that the problem of motivation is not an easy problem, both to understand it and to apply it. This study aims to test whether there is an effect of Compensation, Motivation, Loyalty and Organizational Performance of type B directors in Cibinong. The type of research used in this study is quantitative research. Data collection techniques in this study used survey methods, with closed questionnaires. The population in this study was taken 100 employees. The direct effect of compensation variable on organizational performance is 0.232 and the influence of motivational variable on organizational performance is 0.237. While the indirect role is the motivation variable on organizational performance through loyalty, which is 0.244. And the variable between compensation and organizational performance through loyalty is 0.251. So it can be concluded that the direct effect is still inferior when compared to the indirect effect, so that compensation and motivation influence on organizational performance more on the indirect effect.